Metaproteomic Analysis of Fermented Vegetable Formulations with Lactic Acid Bacteria: A Comparative Study from Initial Stage to 15 Days of Production - Narisa Rueangsri; Sittiruk Roytrakul; Chawanphat Muangnoi; Kullanart Tongkhao; Sudathip Sae-Tan; Khemmapas Treesuwan; Jintana Sirivarasai (Foods)
Research in metagenomics and metaproteomics can reveal how microbiological interactions in fermented foods contribute to their health benefits. This study examined three types of fermented vegetables: a standard formulation, a probiotic formulation with Lacticaseibacillus rhamnosus GG, and a polyphenol formulation with vitexin from Mung bean seed coat. Measurements were taken at day 0 (after 36 h of fermentation at room temperature) and after 15 days. We applied 16S rRNA sequencing to evaluate microbial diversity and utilized LC-MS/MS to investigate the proteomic profiles of specific genera (Lactobacillus and Weissella) and species (Lacticaseibacillus rhamnosus and Levilactobacillus brevis) of lactic acid bacteria (LAB). All of these taxa demonstrated significant relative abundance between 0 and 15 days of fermentation in our metagenomic analysis. Our findings from principal component analysis and clustering analysis categorically distinguished protein expression patterns at various stages of fermentation. By comparing samples from day 0 to day 15, we identified proteins associated with DNA replication and repair mechanisms, including transcription elongation factor GreA, tRNA pseudouridine synthase B, and helicases. We also observed their roles in protein synthesis, which encompasses oxidoreductases and aspartokinase. Furthermore, we identified strong correlations of specific proteins across the three formulations with antioxidant markers. In conclusion, the results of this study decisively enhance our understanding of the role of the proteins related to specific LAB in fermented foods, highlighting their potential to improve texture, flavor, nutritional quality, and health benefits.